An investigation into the anthropogenic effect of biomass energy utilization and economic sustainability on environmental degradation in E7 economies. (18th March 2021) - Gyamfi, Bright Akwasi; Ozturk, Ilhan; Bein, Murad A.; Bekun, Festus Victor
Abstract: Inspired by the Sustainable Development Goals (SDGs), this study focuses on the need for responsible and clean energy consumption, climate change mitigation, and sustainable economic growth. To this end, the study investigates the connection between biomass energy consumption, real GDP, investment in the energy sector, and CO2 emissions in the emerging (E7) countries – China, India, Brazil, Mexico, the Russian Federation, Indonesia and Turkey – for the period 2000–2018. The study uses a battery of techniques, namely Pooled Mean Group‐autoregressive distributed lag, ordinary least square, dynamic ordinary least square, Fully Modified Ordinary Least Squares (PMG‐ARDL, OLS, DOLS FMOLS) and causality estimators, to measure the robustness of the conceptualized relationship among the variables of interest. Empirical results show that conventional energy from fossil fuel sources is a driver of CO2 emissions within the E7 economies. On the other hand, biomass energy consumption and investments in the energy sector decrease CO2 emissions. Furthermore, a feedback causality relationship between biomass energy consumption and CO2 emissions is observed. Similarly, a feedback causality relationship is seen between economic growth and biomass energy consumption. Our study's empirical findings reveal that biomass energy consumption mitigated CO2 emissions in the E7 economies that were examined, suggesting the pivotal role for biomass energy consumption in creating an eco‐friendly environment and environmental sustainability. This requires investment from the private sector, stakeholders, and government administrators in cleaner energy technologies initiatives like biomass. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd